The Effectiveness of Providing Business Capital Loans in Developing Women's Entrepreneurial Soul - RUSANDRY, Rusandry (PT. Keberlanjutan Strategis Indonesia, 2023)
Purpose: Effectiveness is the achievement of organizational goals by efficiently using existing resources in terms of input, process, and output. The problem formulation of this research is to determine the effectiveness of providing business capital loans in developing women's entrepreneurial spirit (PT Esta Dana Ventura, North Maluku, and North Sulawesi) to determine the effectiveness of providing business capital loans in developing women's entrepreneurial spirit.Methodology:The type of research method used in this research is qualitative-descriptive. This method is a form of problem-solving by identifying problems and analyzing the effectiveness of providing business capital loans in developing women's entrepreneurship. In this research, data was obtained from primary data and secondary data. Data reduction, presentation, and conclusion are the data analysis techniques used.Findings: The research results show that based on interviews with the six women above, the effectiveness of providing business capital loans in developing women's entrepreneurial spirit carried out by PT Esta Dana Ventura Manado is quite effective. It is likely effective because the aim of providing business capital loans in the context of developing women's entrepreneurship by PT Esta Dana Ventura Manado has been achieved to empower and prosper members.Implication:However, there needs to be more supervision over the use of loans by members, resulting in borrowers using business capital loan funds not purely for business but for families whose money is only partially for business, resulting in delays in installment payments.